Vitamin A concentrations in dairy cows of Thessaloniki ’s county - CHRISTODOULOPOULOS (Γ. ΧΡΙΣΤΟΔΟΥΛΟΠΟΥΛΟΣ) G.; ROUBIES (Ν. ΡΟΥΜΠΙΕΣ) N.; KARATZIAS (Χ. ΚΑΡΑΤΖΙΑΣ) H.; PAPASTERIADIS (Α. ΠΑΠΑΣΤΕΡΙΑΔΗΣ) A. (Journal of the Hellenic Veterinary Medical Society, 2018)
Avitaminosis A is stilla serius metabolic problem for cattle in Greece. The purpose of this research work was to investigate the blood vitamin A concentrations in dairy cows of Thessaloniki ’s area. The research was conducted in 51 dairy cow farms; whole blood samples from 10 female adult animals per farm, as well as samples from the feedstuffs in use, were collected. Of the total 510 examined cows, 38% showed lower than normal vitamin A concentration in blood plasma (<0,20 μ^ηιΐ), 15% marginal (0,20-0,24 μg/ml) and 47% normal concentration values (>0,25 μg/ml). It should be noted that, of the total 510 examined cows only 7% showed extremely deficient concentration of vitamin A in blood plasma (<0,05 μg/ml). The determination of total carotene concentration in feedstuffs from those farms, indicated that only the corn ensilage and the fresh grass contained the appropriate amount of carotene. The above results, in correlation with corresponding results from previous researches, indicate that there is a decrease in the percentage of cows with subnormal vitamin A concentration. This may be attributed to more frequent use of corn silage, and more systematic addition of vitamin A in concentrate feeds. This research provides evidence that some dairy cow genotypes, with high milk yields, may balance their needs only by vitamin A supplementation, it means that maybe the ration carotenes alone are no sufficient vitamin A source for these cows. Furthermore, the results of this research suggest that the absence of a regulator mechanism for the carotene concentration in the cattle blood plasma may be possible.